2021
DOI: 10.1101/2021.05.15.444262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety, immunogenicity and protection provided by unadjuvanted and adjuvanted formulations of recombinant plant-derived virus-like particle vaccine candidate for COVID-19 in non-human primates

Abstract: Although antivirals are important tools to control the SARS-CoV-2 infection, effective vaccines are essential to control the current pandemic. Plant-derived virus-like particle (VLP) vaccine candidates have previously demonstrated immunogenicity and efficacy against influenza. Here we report the immunogenicity and protection induced in macaques by intramuscular injections of VLP bearing SARS-CoV-2 spike protein (CoVLP) vaccine candidate formulated with or without Adjuvant System 03 (AS03) or cytosine phosphogu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Although most human CXR examinations are inconclusive during the early stages of COVID-19 [37], 28 studies of SARS-CoV-2-exposed NHPs detected CXR abnormalities early after exposure [9,[13][14][15][16][17][20][21][22][23]26,27,29,32,35,[44][45][46]. However, CXR imaging was inconclusive in other studies [12,13,[23][24][25]28] and was generally found to be uncorrelated with the degree of lung abnormalities at necropsy (Figure 1).…”
Section: Highlightsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most human CXR examinations are inconclusive during the early stages of COVID-19 [37], 28 studies of SARS-CoV-2-exposed NHPs detected CXR abnormalities early after exposure [9,[13][14][15][16][17][20][21][22][23]26,27,29,32,35,[44][45][46]. However, CXR imaging was inconclusive in other studies [12,13,[23][24][25]28] and was generally found to be uncorrelated with the degree of lung abnormalities at necropsy (Figure 1).…”
Section: Highlightsmentioning
confidence: 99%
“…Multiple routes [9,13,16,20,23,26,28,29,31,33,34,46] lead to SARS-CoV-2 shedding. However, although infection is not necessarily dependent on respiratory tract exposure, it is plausible that the route of exposure impacts the progression of disease.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many consider NAb levels to be a good candidate for a correlate of protection [81] , this is a fairly limited evaluation of vaccine-induced immunity and it is very likely that non-neutralizing but functional antibodies and cellular responses also contribute to vaccine-induced protection [82] . Data from a large non-human primate study [83] as well as ongoing clinical trials [27] , [65] , [84] demonstrate that AS03-adjuvanted CoVLP stimulates multiple arms of the adaptive response to SARS-CoV-2. Results from Medicago’s ongoing pivotal Phase 3 efficacy study [25] (NCT04636697), performed in different regions of the world where several VOCs have been circulating, demonstrated a good protection of the CoVLP vaccine (targeting the ancestral strain) against several VOCs such as B.1.617.2 and P.1.…”
Section: Discussionmentioning
confidence: 99%